Trabalhando a relação senso comum e ciência nas aulas de filosofia do ensino médio a partir do pensamento de Rubem Alves - Costa, Márcia Araújo da (2022)
The present work intends to reflect on the relationship between common sense and science as I have been teaching philosophy during my high school classes at the Escola Estadual de Educação Profissional Juarez Távora in Fortaleza, Ceará. To this end, I used the thought of the philosopher and educator Rubem Alves as a conductor for the research, especially in his book Filosofia da Ciência: Introdução ao jogo e suas regras (1981). The proximity with Alves' work is due to the fact that this thinker brings an approach that does not belittle or exclude common sense in its relationship with science. In general, the notion of common sense is discredited because it is understood as a space of ignorance, vulgar opinion, or superstitious belief. However, it is from this common sense that the students' primary ways of thinking emerge, and to suppress and totally disregard this way of thinking is to "cut" the roots of the knowledge and experiences that the students bring to the "school ground". Rubem Alves, in this context, conveys the idea that the knowledge of science is common sense, certainly in a more refined, elaborated and disciplined form. This term gains such consistency in the thought and words of Rubem Alves that it ends up being characterized as the basis of the whole scientific process. In his words: "science is common sense hypertrophied". Such ideas were fundamental to show the students that they already think in a similar way to a scientist when solving problems and that their fears regarding the "men in white coats" and their laboratories are, for the most part, unfounded. On the contrary, it was noticed an "empowerment" of the students from the reflections about common sense in Rubem Alves. In this sense, bringing such reflections about common sense and science to the classroom, in a philosophy class, was fundamental in the realization of practical activities, described in this paper, which aimed to instigate scientific experiences in the students. The practices related to the Phytotherapy project and the perceptions around the so-called "Rain Prophets" showed the students how popular knowledge and science are forms of knowledge that do not exclude each other, but intertwine and cooperate for a greater and better understanding of life and the world.